PRODUCTION OF GLASS-CERAMICS FROM WASTE MATERIALS AND OPTIMIZATION OF THE MAIN PROCESS PARAMETERS - Angjusheva, B.; Fidancevski, E.; Lisichkov, K.; Jovanov, V. (Journal of Engineering & Processing Management, 2016)
In this study the 3D surface model was successfully applied in investigating the influence of the process parameters on the physical and mechanical properties of the glass-ceramics. Glassceramics was produced from coal fly ash and waste glass through the sintering method. The raw material was taken from “REK Bitola”, a thermal power plant in the Republic of Macedonia. Glass-ceramics was obtained through the process of consolidation. Compacts with different ratio of fly ash and waste glass were pressed at 45 MPa, sintered in the temperature interval from 1000 to 11000C, and isothermal time at the final temperature from 1h to 5h. The process of optimization was conducted on the process parameters such as quantity of glass, sintering temperature and isothermal time. According to the results of the process of optimization presented by the software package, a final model equations of the density and bending strength dependence were obtained.